Prenatal Education within the Cultural Beliefs of the Matrilineal Society: An Ethnopedology Perspective - Ridha Hasnul Ulya; Ineng Naini; Dewirahmadanirwati; Jasril (Journal of Education Research, 2026)
This study aims to explore the pedagogical dimensions of prenatal education embedded in the superstitious beliefs of the Minangkabau community. Prenatal education is viewed as a fundamental foundation for shaping fetal character and well-being from the earliest stages of pregnancy. A descriptive qualitative approach with an ethnographic design was employed. Primary data were collected through in-depth interviews and participant observations involving 33 traditional leaders, 13 parents, and 13 pregnant women in Solok Regency. The data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing, while source triangulation ensured data credibility. The findings reveal that traditional prohibitions, such as avoiding chipped plates, refraining from placing cloth around the neck, and not sitting on doorsteps, function as informal pedagogical practices that regulate maternal behavior to promote physical safety, emotional stability, and social values during pregnancy. These findings highlight the relevance of integrating Minangkabau local wisdom with contemporary parenting education to develop culturally grounded and holistic family education models.